Astragalus mongholicus (Fisch.) Bge Improves Peripheral Treg Cell Immunity Imbalance in the Children With Viral Myocarditis by Reducing the Levels of miR-146b and miR-155 - Zhang, Zhen; Dai, Xinlun; Qi, Ji; Ao, Yu; Yang, Chunfeng; Li, Yumei (Frontiers in Pediatrics, 2018)
Viral myocarditis (VMC) is a common cardiac disease, however, there still lacks an effective therapeutic strategy for VMC. Astragalus mongholicus (Fisch.) Bge (AB), a Chinese herb with some functional metabolites, may have some pharmacological effects on VMC. AB ingredients were measured by a full-scan LCQ mass spectrum. We aimed to explore the effects of AB on the VMC children by investigating peripheral Treg cell homeostasis. A total of 68 VMC children were random and evenly assigned into an AG group (received 10-mL AB oral liquid daily), and a CG group (received placebo daily). Peripheral blood mononuclear cells (PBMC) were obtained from peripheral blood and Treg cells were isolated. The levels of miR-146b, miR-155, Treg immunity activity and myocarditis biomarkers were measured in Treg cells. There were four main components (sucrose, calycosin, Astragaloside IV and calycosin-7-glucoside) in AB. The cases sinus tachycardia, frequent premature ventricular contractions, and supraventricular tachycardia were significantly reduced in the AG group (P < 0.05). Meanwhile, the myocardial enzymes and cardiac function indexes were improved in the AG group when compared with the CG group (P<0.05). The time of electrocardiogram recovery, symptom duration and hospital stay was shorter in the AG group than in the CG group (P<0.05). The levels of miR-146b and miR-155 were higher in the CG group than in the AG group (P<0.05). The levels of ROR-γt (retinoic acid receptor-related orphan nuclear receptor gamma), FoxP3 (forkhead transcription factor), IL-10 (interleukin-11) and TGF-β (transforming growth factor beta) were lower in the CG group than in the AG group (P<0.05). In contrast, the levels of IL-17, IL-21, CK-MB (creatine kinase-MB), cTnI (cardiac troponin I), GrB (granzyme B), sFasL (soluble fas ligand) and caspase-3 were higher in the CG group than in the AG group (P<0.05). Furthermore, the levels of ROR-γt, FoxP3, IL-10 and TGF-β were positively, whereas the levels of IL-17, IL-21, CK-MB, cTnI, GrB, sFasL and caspase-3 were negatively, associated with the levels of miR-146b and miR-155 (P<0.05). AB treatment improved cardiac functions, peripheral Treg cell immunity imbalance in the children with VMC by reducing the levels of miR-146b and miR-155.